G433(P) Trainees shape a new teaching schedule. (May 2019) - Syrimi, E; Brothwell, SLC; Bogue, D; Kelly, L; Hine, C; Goodyear, H
Abstract : Aim: Teaching of trainees is an essential aspect of Paediatric training, ensuring that all competences are met in order to gain a certificate of completion of training. Looking at our regional Level 1 (ST1–3) teaching programme, the majority of teaching at protected monthly teaching days was lecture-based. This study looked at trainees' views of regional teaching and aimed to create a backbone for any change required. Methods: We designed and circulated a questionnaire for level 1 and 2 (ST4–5) trainees. Level 2 trainees were included in order to receive a more holistic view of both current and past training. The questionnaire was anonymous and collected by the Postgraduate training administrator at the end of regional teaching days. Results: A total of 80 completed questionnaires were obtained from trainees: 8 in ST1, 21 in ST2, 13 in ST3 and 38 in ST4–5 with a response rate of 73% (80/110). Mean satisfaction rating for the quality of teaching for all three years (ST1–3) was 4.5/6. The majority of trainees had completed all paediatric training in our region (91%; n=73). Responses were concentrated on location (14%), emphasising the need for central location of teaching days within our region which is geographically large. Many trainees (37%; n=30) fed back that they would like their teaching days to be more interactive with small group sessions, cased-based discussions, practical sessions and communication scenarios. Trainees had many useful suggestions as to how regional teaching sessions could potentially be improved. We subsequently established a trainee-led teaching committee to oversee change including incorporating group sessions that promote leadership, communication and practical skills into the programme to prepare trainees to be future medical leaders. Conclusion: Even when a training programme evaluates well, it is important to continuously seek trainee opinion to tailor learning, make it learner-centred and help trainees meet the curriculum requirements. The trainee-led teaching committee has already established new teaching sessions to complement the existing programme, with further sessions planned. This study reinforces the importance of engaging trainees and encouraging them to act as agents of change to improve training.